Implementation of ARIMA with Min-Max Normalization for predicting the Price and Production Quantity of Red Chili Peppers in North Sumatra Province considering Rainfall and Sunlight Duration Factors - Prihandi, Ifan; Wijono, Sutarto; Sembiring, Irwan; Maria, Evi (Engineering, Technology & Applied Science Research, 2025)
Red chili peppers are a vital agricultural commodity in the North Sumatra province, playing a significant role in Indonesia's economy. Fluctuations in chili prices affect farmers, consumers, and overall economic stability. This study leverages time series forecasting using the ARIMA model to predict red chili pepper prices and production, incorporating weather factors such as rainfall and sunlight duration. The dataset spans March 2021 to December 2023 and includes historical records of chili prices, production levels, and weather conditions. The analysis reveals a strong correlation between price fluctuations and production trends: Prices tend to rise when production declines and fall when yields increase. Additionally, production is influenced by weather conditions, where excessive rainfall damages crops and reduces yields, while balanced rainfall and sunlight duration support optimal growth. The ARIMA model demonstrates its effectiveness in capturing these patterns, providing actionable insights for farmers and policymakers to predict price changes and optimize production strategies. By integrating data-driven forecasting with weather analysis, this research contributes to more adaptive and informed decision-making in the agricultural sector.